Commutability Assessment of Candidate Reference Materials for Pancreatic α-Amylase. (1st August 2018) - Deprez, Liesbet; Toussaint, Brigitte; Zegers, Ingrid; Schimmel, Heinz; Grote-Koska, Denis; Klauke, Rainer; Gella, F Javier; Orth, Matthias; Lessinger, Jean-Marc; Trenti, Tommaso; Nilsson, Göran; Ceriotti, Ferruccio
Abstract: BACKGROUND: Measurement standardization of the catalytic concentration of α-amylase in serum is based on 3 pillars: the primary reference measurement procedure (PRMP), reference laboratories, and suitable certified reference materials (CRMs). Commutability is a prerequisite when using a CRM for calibration and trueness control of routine methods or for value transfer from the PRMP to end-user calibrators of routine methods through a calibration hierarchy. METHODS: We performed a commutability study with 30 serum pools and 5 candidate reference materials (RMs) for pancreatic α-amylase using an automated version of the PRMP and 5 different routine methods. Four candidate RMs had an artificial matrix, each with a different composition, and 1 candidate RM was based on human serum. Data were analyzed according to a linear regression analysis with prediction interval as described in the Clinical and Laboratory Standards Institute guideline EP30-A and a difference in bias analysis as described in the recommendations of the IFCC Working Group on Commutability. RESULTS: The commutability profile of the 4 candidate RMs with an artificial matrix was variable. Only 1 candidate RM, with human serum albumin in the matrix, showed a good profile like that of the candidate RM based on serum. The comparison of both commutability assessment approaches indicated some differences because of inconclusive results for the difference in bias approach, suggesting a large uncertainty on the commutability assessment. CONCLUSIONS: A CRM for pancreatic amylase in an artificial matrix can be commutable for routine methods using the same substrate as the PRMP, but the matrix composition is crucial.